Recent advances in macrocyclic arenes-based fluorescent indicator displacement assays - Duan, Qunpeng; Wang, Fei; Lu, Kui (Frontiers in Chemistry, 2022)
Macrocyclic arenes-based fluorescent indicator displacement assays (F-IDAs) offer a unique and innovative approach to chemosensing, taking molecular recognition in host-guest chemistry to a higher level. Because of their special architecture and versatile host-guest binding properties, macrocyclic arenes, principally calix[n]arenes and, in recent years, pillar[n]arenes, in combination with various fluorophores, are widely used in F-IDAs for the specific and selective sensing of cationic, anionic, and neutral analytes. In this paper, we review recent progress in the development of F-IDAs based on macrocyclic arenes and outline the prospects and remaining challenges relating to macrocyclic arenes-based F-IDAs.